Answer:
g/f = {(-1, 2)}
domain of g/f = {-1}
Explanation:
Given,
f = {(-1, 4),(1, 9),(4, 0)},
g = {(-1, -8),(2, -7),(4, 8),(5, -9)}
So, Domain of f = {-1, 1, 4},
Domain of g = {-1, 2, 4, 5}
Since,
![(g)/(f)(x) = (g(x))/(f(x))](https://img.qammunity.org/2020/formulas/mathematics/college/fmcn7zzdjrcyi6rt8ksllji39i7py3141e.png)
Thus, domain of g/f = Domain of f ∩ Domain of g = {-1, 4}
If x = -1,
![(g)/(f)(-1) = (g(-1))/(f(-1))=(-8)/(-4)=2](https://img.qammunity.org/2020/formulas/mathematics/college/2zyyiuirrwdu4x7ivnbklctw5qqu3uxxys.png)
If x = 4,
![(g)/(f)(4) = (g(4))/(f(4))=(8)/(0)=\infty (\text{ not possible})](https://img.qammunity.org/2020/formulas/mathematics/college/inv3hslr0maqdzm871kdle09cqu4hz4ciu.png)
Hence, the domain of g/f = {-1}
And, g/f = {(-1, 2)}